2020
DOI: 10.1002/hed.26095
|View full text |Cite
|
Sign up to set email alerts
|

Anatomically‐based transoral surgical approach to early‐stage oral tongue squamous cell carcinoma

Abstract: The mainstream of treatment of early-stage oral tongue squamous cell carcinoma (OTSCC) is represented by transoral resection with "adequate" free margins. Despite that, a precise and shared definition of "adequate margin" is lacking, and so is a standardized transoral surgical technique.The tongue is a symmetrically paired organ, consisting of intertwining intrinsic and extrinsic muscles, which can be distinguished during dissection. Routes of tumoral spread in oral tongue cancer are well-known and should be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…And it enables surgical resection with enough margin simultaneously with primary repair and also leave minimal cosmetic and functional defects. 13) Presence of neck lymph node metastasis is one of the most important prognostic factors of head and neck cancer. Classic or modified radical neck dissection is a treatment of choice of nodal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…And it enables surgical resection with enough margin simultaneously with primary repair and also leave minimal cosmetic and functional defects. 13) Presence of neck lymph node metastasis is one of the most important prognostic factors of head and neck cancer. Classic or modified radical neck dissection is a treatment of choice of nodal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…As a common and highly malignant oral squamous cell carcinoma, tongue squamous cell carcinoma (TSCC) [1] TSCC can easily lead to disorders of swallowing, chewing, speech thereby seriously influencing the quality of life of the patient [2]. It also has a poor prognosis and a high local recurrence rate, which lead to reduced overall survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chandler et al showed that local recurrence was higher with muscle invasion than DOI, although the positive predictive value of muscle invasion in regards to nodal status was slightly less than DOI [7]. Additionally, routes of tumoral spread in the oral tongue through muscle fibers should be taken into account to plan a complete resection through a standardized and replicable surgical technique [8]. Therefore, it is interesting to compare the aspects of tumor diffusion in lingual musculature on the basis of anatomical and surgical findings with the most recent basic research data [9].…”
Section: Introductionmentioning
confidence: 99%